Amorphous V–O–C composite nanofibers electrospun from solution precursors as binder- and conductive additive-free electrodes for supercapacitors with outstanding performance - Chen, Xia; Zhao, Bote; Cai, Yong; Tade, Moses; Shao, Zongping (R S C Publications, 2013)
Flexible V–O–C composite nanofibers were fabricated from solution precursors via electrospinning and were investigated as free-standing and additive-free film electrodes for supercapacitors. Specifically, composite nanofibers (V0, V5, V10 and V20) with different vanadyl acetylacetonate (VO(acac)2) contents of 0, 5, 10 and 20 wt% with respect to polyacrylonitrile (PAN) were prepared. The composite nanofibers were comparatively studied using XRD, Raman spectroscopy, XPS, N2 adsorption–desorption, FE-SEM, TEM and S-TEM. The vanadium element was found to be well-dispersed in the carbon nanofibers, free from the formation of an aggregated crystalline phase, even in the case of V20. A specific surface area of 587.9 m2 g-1 was reached for V10 after calcination, which is approximately twice that of the vanadium-free carbon nanofibers (V0, 300.9 m2 g-1). To perform as an electrode for supercapacitors in an aqueous electrolyte, the V10 film delivered a specific capacitance of 463 F g-1 at 1 A g-1. V10 was also able to retain a specific capacitance of 380 F g-1, even at a current density of 10 A g-1. Additionally, very stable cycling stability was achieved, maintaining an outstanding specific capacitance of 400 F g-1 at 5 A g-1 after charge–discharge cycling 5000 times. Thus, V–O–C composite nanofibers are highly attractive electrode materials for flexible, high-power, thin film energy storage devices and applications.